CORPORATE IMAGE MANAGEMENT AND EFFECTIVENESS OF TELECOMMUNICATIONS COMPANIES (American Journal of Interdisciplinary Research and Development, 2023)
This study investigates the link between organizational effectiveness, as measured by client acquisition and corporate image management, which is accomplished through corporate identity and reputation. A cross-sectional survey was used to collect data from 209 consumers of different telecommunication companies. The data was analyzed using descriptive and inferential statistics, including Pearson's product moment correlation. The study's findings showed a link between corporate image management and organizational success, as evidenced by a substantial and positive correlation between CEM components and organizational performance measures. Unlike previous findings, the study's conclusion presented solid proof of a company's reputation and identity having a major influence on word-of-mouth marketing and client acquisition. In practice, the study stressed how important it is to manage your company's image and brand strategically in order to attract new clients and promote goodwill. Moreover, the findings offer theoretical backing for the connections among corporate identity, corporate reputation, and organisational success, enhancing the current body of literature and directing future investigations. The research suggests that organizations should prioritize the development and maintenance of a trustworthy corporate identity.